2022
DOI: 10.7759/cureus.21850
|View full text |Cite
|
Sign up to set email alerts
|

IgG4-Related Disease Presenting as Hypertrophic Pachymeningitis

Abstract: IgG4-related disease (IgG4-RD) is a multi-organ, immune-mediated inflammatory condition of unknown etiology characterized by infiltration of tissues by IgG4 producing plasma cells. IgG4-related disease (IgG4-RD) can ideally affect any organs, but the involvement of the central nervous system (CNS) is a rare entity. We present a case of a 67-year-old male who presented with diplopia with imaging showing hypertrophic pachymeningitis (HPM) and was diagnosed with IgG4-RD of the CNS based on histopathology report.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Meningeal involvement may be contiguous with disease in the orbit or pituitary gland and these patients may show elevations of cerebrospinal fluid IgG4 level, indicating intrathecal production of IgG4. On MRI, the dura may show smooth thickening with homogeneous diffuse linear enhancement (as in the case presented), or focal nodular thickening, mimicking a meningioma, and may result in compression of surrounding structures, especially cranial nerves [15].…”
Section: Discussionmentioning
confidence: 73%
“…Meningeal involvement may be contiguous with disease in the orbit or pituitary gland and these patients may show elevations of cerebrospinal fluid IgG4 level, indicating intrathecal production of IgG4. On MRI, the dura may show smooth thickening with homogeneous diffuse linear enhancement (as in the case presented), or focal nodular thickening, mimicking a meningioma, and may result in compression of surrounding structures, especially cranial nerves [15].…”
Section: Discussionmentioning
confidence: 73%
“…CNS-IgG4-RD [10] Central nervous system and systemic involvement (e.g., pancreas, salivary glands, kidneys, lungs) Periorbital pseudotumor, pituitary inflammation, diffuse intracranial dural/dural thickening or masses.…”
Section: Systemic Manifestations Radiological Features Histopathology...mentioning
confidence: 99%
“…12 Apart from the best-known manifestations of IgG4-RD in the major salivary glands, lacrimal glands and thyroid (i.e., Riedel's thyroiditis), there is an increasing number of reports describing the involvement of extraglandular tissues, such as extraorbital muscles, orbital nerves, meninges, sinonasal tract, trigeminal nerve branches, skin, ears, and larynx. [13][14][15][16][17][18][19] The oral cavity is not among the commonly reported locations in the head and neck area, and its involvement is often neglected in most reviews dealing with this topic, thus organ-specific features have not yet been identified in the international diagnostic criteria for IgG4-RD. 20 For these reasons, it is of the utmost importance that oral medicine physicians, head and neck surgeons, and oral and maxillofacial pathologists be familiar with the clinicopathological manifestations of IgG4-RD in the oral cavity, in order to avoid misdiagnosis and extensive surgical resections that may impair the patient's quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…This is the case of Mikulicz's disease (MD), which is characterized by bilateral enlargement of lacrimal and salivary glands, 11 or chronic sclerosing sialadenitis (Küttner's tumor, KT), which usually presents as a firm swelling of the submandibular gland 12 . Apart from the best‐known manifestations of IgG4‐RD in the major salivary glands, lacrimal glands and thyroid (i.e., Riedel's thyroiditis), there is an increasing number of reports describing the involvement of extraglandular tissues, such as extraorbital muscles, orbital nerves, meninges, sinonasal tract, trigeminal nerve branches, skin, ears, and larynx 13–19 . The oral cavity is not among the commonly reported locations in the head and neck area, and its involvement is often neglected in most reviews dealing with this topic, thus organ‐specific features have not yet been identified in the international diagnostic criteria for IgG4‐RD 20 …”
Section: Introductionmentioning
confidence: 99%